Immunological reference intervals in pregnancy: longitudinal analysis of adaptive lymphocyte subsets - Ângelo-Dias, Miguel; Martins, Catarina Gregório; Mata, Mariana; Barata, Madalena; Chung, Ana; Sarzedas, Susana; Fernandes, Élia; Appleton, Cláudia; Lima, Jorge; Borrego, Luis Miguel (Frontiers in Immunology, 2025)
BackgroundPregnancy induces profound immunological adaptations necessary to support fetal development while preserving maternal health. However, the systemic dynamics of less-studied adaptive immune cell subsets across gestation remain incompletely understood.ObjectiveWe have conducted a comprehensive longitudinal analysis of peripheral B and T cell populations in healthy pregnant women in order to identify trimester-specific immune changes and to establish reference intervals for clinical and research use.MethodsA total of 50 pregnant and 30 age-matched non-pregnant women were recruited in a prospective cohort study. Peripheral blood was collected at each trimester and analyzed by high-dimensional flow cytometry. We evaluated 74 lymphocyte subsets, including follicular and non-follicular CD4 and CD8 T cells, and functional markers CD69 and PD-L1, under basal and stimulated conditions.ResultsPregnancy was associated with decreased total B cell counts, particularly within transitional and anergic naïve subsets, and increased activated naïve and memory B cells. T cell activation progressively increased in CD4 and CD8 subsets, especially during late pregnancy. Notably, activated circulating follicular helper T cells (cTfh) were consistently reduced throughout gestation compared to controls, while CD69 and PD-L1 expressions on CD4 and CD8 T cells increased in the third trimester. Maternal factors, including age, parity, miscarriage history, and BMI, significantly influenced specific immune profiles. Reference intervals were established for key subsets, and deviations in women who experienced pregnancy complications suggest potential predictive value for future risk assessment.ConclusionsOur findings provide novel insights into the systemic immune adaptations that occur during pregnancy, particularly concerning follicular and non-follicular lymphocyte subsets. The proposed reference ranges proposed may serve as valuable tools for immunomonitoring and for identifying pregnancies at risk.